KARAKTERISASI SIFAT FUNGSIONAL KONSENTRAT PROTEIN IKAN SUNGLIR (Elagatis bipinnulatus) - Frets Jonas Rieuwpassa; Ely John Karimela; Devitha Cindy Lasaru (Fakultas Perikanan dan Ilmu Kelautan, 2018)
Fish protein Concentrat (FPC) is a form of dry protein wich is extracted from fish meet using ethanol solvent. The aims of this research is to characterization of fish protein concentrate wich extraction using ethanol 90%. There are some steps that we established to achieve the aims such as (1) FPC exctraction using etanol 90% with ratio 1 : 3 during 3 hours, (2) to determine of characterization of FPC. All data are given descriptively. Result show the mean of FPC rendement between 20%. Characteristic base on FAO 1976 showed protein (85%), fat (3,28%), odor (2,11: strong fishy odor) and whiteness degree (53,54%) based on the information this product chategorized as type B. water contain analysis (6, 34%), asses (7,47%), functional properties: oil absorbant capacity (2,48 g/g) and water absorbant capacity (2,02 ml/g). This product contained 9 essential amino acids and 6 non essential amino acids.